ANALISIS PENGELOLAAN KEUANGAN SYARIAH DALAM MENINGKATKAN TRANSPARANSI PADA YAYASAN PENDIDIKAN ISLAMIC BOARDING SCHOOL AL-ANWAR PETANANG KUMPEH - Windayani, Windayani; Usdeldi, Usdeldi; Muthmainnah, Muthmainnah (Nusantara Hasana Journal, 2026)
This study is entitled “Analysis of Sharia Financial Management in Enhancing Transparency at the Islamic Boarding School Education Foundation Al-Anwar Kumpeh.” The background of this research emphasizes the importance of implementing sharia financial management in Islamic educational institutions to create transparency, accountability, and financial governance aligned with Islamic values. The purpose of this study is to analyze the financial management system, identify existing obstacles, and find solutions to improve financial transparency at the Al-Anwar Foundation. This research employs a descriptive qualitative method, with data collection techniques including interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The results show that financial management at the Al-Anwar Foundation has implemented sharia principles such as trustworthiness (amanah), justice, and hisbah through participatory budgeting and record-keeping based on written evidence. However, several obstacles remain, including limited human resources, manual recording systems, and unstable funding income. The foundation addresses these challenges by setting budget priorities, providing sharia financial management training, and implementing social policies for underprivileged students. This study concludes that sharia financial management at the Al-Anwar Foundation has been carried out well; however, improvements in professional capacity and financial system digitalization are still needed to strengthen transparency.